2017
DOI: 10.1002/2017ja024488
|View full text |Cite
|
Sign up to set email alerts
|

The MMS Dayside Magnetic Reconnection Locations During Phase 1 and Their Relation to the Predictions of the Maximum Magnetic Shear Model

Abstract: Several studies have validated the accuracy of the maximum magnetic shear model to predict the location of the reconnection site at the dayside magnetopause. These studies found agreement between model and observations for 74% to 88% of events examined. It should be noted that, of the anomalous events that failed the prediction of the model, 72% shared a very specific parameter range. These events occurred around equinox for an interplanetary magnetic field (IMF) clock angle of about 240°. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 64 publications
1
56
0
Order By: Relevance
“…Here we use the maximum magnetic shear model by Trattner et al () to estimate the possible source region of FTE cascades. The FTE cascades in our study appear during those IMF conditions (southward IMF with a strong B y component) for which the maximum magnetic shear model gives an excellent agreement with observations of normal reconnection events (Trattner et al, , , , ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Here we use the maximum magnetic shear model by Trattner et al () to estimate the possible source region of FTE cascades. The FTE cascades in our study appear during those IMF conditions (southward IMF with a strong B y component) for which the maximum magnetic shear model gives an excellent agreement with observations of normal reconnection events (Trattner et al, , , , ).…”
Section: Discussionsupporting
confidence: 89%
“…There exist both observational studies (e.g., Trenchi et al, ) and magnetohydrodynamic simulations (Hoilijoki et al, ) confirming such a dipole tilt‐dependent shift of the reconnection line toward the winter hemisphere. Comparing the maximum magnetic shear model with reconnection signatures in Polar (Trattner et al, ), Time History of Events and Macroscale Interactions during Substorms (THEMIS) (Trattner et al, ), and Magnetic Multiscale Mission (MMS) data (Trattner et al, ) showed an excellent agreement with observations for a large majority of cases. Deviations between model and observations occur though for specific IMF conditions.…”
Section: Introductionmentioning
confidence: 83%
“…The model also predicts that during IMF clock angles (arctan ( B Y / B Z ), where 0° is defined as pointing due north) within ±25° of a southward magnetic field or events occurring during a mainly radial magnetic field (IMF| B X |/ B > 0.7) the reconnection process reverts to an antiparallel reconnection scenario with no component reconnection tilted X‐line present. Several magnetopause reconnection studies and MHD simulations have successfully used and confirmed the model predictions (e.g., Dunlop et al, ; Fuselier et al, ; Komar et al, ; Petrinec et al, ; Trattner et al, 2012, Trattner, Thresher, et al, , Trattner, Burch, et al, ; Vines et al, ).…”
Section: Introductionmentioning
confidence: 84%
“…Figure shows the distance of the 302 MMS X‐line encounters observed during Phase 1a (Trattner, Burch, et al, ) from the predicted reconnection location versus the IMF clock angles of the events. While 80% of the events are within the model uncertainty of 2 R E (dotted line), the IMF clock angles around 120° and 240° showed larger errors and are associated with the fall and spring equinoxes, respectively.…”
Section: Observationsmentioning
confidence: 99%
“…One empirical model that has been very successful in predicting where reconnection X‐lines occur and where there is antiparallel and component reconnection is the maximum shear reconnection model (Trattner et al, , ). This model was developed from a large number of measurements in the Earth's magnetospheric cusps and has been tested successfully using in situ observations at the Earth's magnetopause (Dunlop et al, ; Fuselier et al, ; Petrinec et al, ; Trattner et al, ; Trattner et al, ) and using energetic neutral atom observations to remotely image the magnetospheric cusps (Petrinec et al, ). The model was used successfully to predict the reconnection diffusion region encounters by the Magnetospheric Multiscale (MMS) mission (Fuselier et al, ).…”
Section: Introductionmentioning
confidence: 99%